"It's all about asking from those who have walked the path": Patient and stakeholder perspectives on how peers may shift substance use stigma in HIV care in South Africa. - Magidson, Jessica F; Rose, Alexandra L; Regenauer, Kristen S; Brooke-Sumner, Carrie; Anvari, Morgan S; Jack, Helen E; Johnson, Kim; Belus, Jennifer M; Joska, John; Bassett, Ingrid V; Sibeko, Goodman; Myers-Franchi, Bronwyn (2022)
BACKGROUND: South Africa has the highest number of people with HIV (PWH) globally and a significant burden of co-occurring substance use disorder (SUD). Health care worker (HCW) stigma towards SUD is a key barrier to HIV care engagement among PWH with SUD. Support from peers-individuals with lived experience of SUD-may be a promising solution for addressing SUD stigma, while also improving engagement in HIV care. We evaluated the perceived acceptability of integrating a peer role into community-based HIV care teams as a strategy to address SUD stigma at multiple levels and improve patient engagement in HIV care.